2016
DOI: 10.1186/s12889-016-3404-3
|View full text |Cite
|
Sign up to set email alerts
|

Subnational variation for care at birth in Tanzania: is this explained by place, people, money or drugs?

Abstract: BackgroundTanzania achieved the Millennium Development Goal for child survival, yet made insufficient progress for maternal and neonatal survival and stillbirths, due to low coverage and quality of services for care at birth, with rural women left behind. Our study aimed to evaluate Tanzania’s subnational (regional-level) variations for rural care at birth outcomes, i.e., rural women giving birth in a facility and by Caesarean section (C-section), and associations with health systems inputs (financing, health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…11 Researchers have found that women with high screening rates have increased chances of early diagnosis and early treatment. 10 A woman's level of education, 13,14 perception regarding her vulnerability to HPV infection, 15 low socioeconomic status, 13,16 residential setting (rural or urban) , 16,17 and young age 14,18 are factors associated with knowledge about HPV infection and cervical cancer. Knowledge about cervical cancer, 19,20 income levels, 21 fear of Pap smear, 22 age, 19,23 place of residence, 23 and distance to the nearest facility providing cervical cancer screening 20 are factors that influence cervical cancer screening uptake.…”
Section: Introductionmentioning
confidence: 99%
“…11 Researchers have found that women with high screening rates have increased chances of early diagnosis and early treatment. 10 A woman's level of education, 13,14 perception regarding her vulnerability to HPV infection, 15 low socioeconomic status, 13,16 residential setting (rural or urban) , 16,17 and young age 14,18 are factors associated with knowledge about HPV infection and cervical cancer. Knowledge about cervical cancer, 19,20 income levels, 21 fear of Pap smear, 22 age, 19,23 place of residence, 23 and distance to the nearest facility providing cervical cancer screening 20 are factors that influence cervical cancer screening uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers operate to reduce supply, affordability and availability of these services. These include out-of-pocket health expenditures [33], inattention to reproductive health and rights [37], poor quality of health care [37], inadequate staffing [38], and lack of training of health providers [36], fear of being neglected or maltreated by health workers [34,36]. Our study adds onto existing literature showing that women who inject drugs may particularly be affected by these barriers [23,26,39].…”
Section: Discussionmentioning
confidence: 85%
“…The important geographic variation in caesarean readiness mirrors documented differences in delivery care capability 3 41 42 and maternal mortality, 43 although all regions are critically under-resourced in workforce and essential health commodities. 22 Despite maternal health having high political priority since the 1990s in Tanzania, programmatic implementation across regions was found to be inconsistent. 28 …”
Section: Discussionmentioning
confidence: 99%
“…19 Within facilities, readiness for and availability of emergency obstetric care is low 3 20 (particularly in health centres 21 ) and varies across regions. 22 …”
Section: Introductionmentioning
confidence: 99%